2021
DOI: 10.3390/ijms22179263
|View full text |Cite
|
Sign up to set email alerts
|

BGP-15 Inhibits Hyperglycemia-Aggravated VSMC Calcification Induced by High Phosphate

Abstract: Vascular calcification associated with high plasma phosphate (Pi) level is a frequent complication of hyperglycemia, diabetes mellitus, and chronic kidney disease. BGP-15 is an emerging anti-diabetic drug candidate. This study was aimed to explore whether BGP-15 inhibits high Pi-induced calcification of human vascular smooth muscle cells (VSMCs) under normal glucose (NG) and high glucose (HG) conditions. Exposure of VSMCs to Pi resulted in accumulation of extracellular calcium, elevated cellular Pi uptake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Terpinen-4-ol hinders posttranslational PERK formation at the K889 acetylation site by increasing SIRT1 expression and improving VC by regulating the ER pressure [ 89 ]. Interleukin enhancer binding factor 3 (ILF3) expression was found to be increased in calcified human aortic vascular smooth muscle cells (HAVSMCs) and calcified atherosclerotic plaques in humans and mice, and ILF3 promoted atherosclerotic calcification by acting on the promoter regions of BMP2 and STAT1 and mediating BMP2 upregulation and STAT1 downregulation, according to Fei Xie et al [ 90 ] BGP-15 is an emerging antidiabetic drug that has been found to inhibit Pi-induced phenotypic transformation during the osteochondrogenesis and mineralization of VSMCs, making it potentially ideal for reducing diabetic and nondiabetic vascular calcification [ 91 ]. In vitro experiments demonstrated that miR-223-3p blocked interleukin 6 (IL-6)/STAT3 signaling, thereby preventing osteogenic transformation and calcification in VSMCs [ 92 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Terpinen-4-ol hinders posttranslational PERK formation at the K889 acetylation site by increasing SIRT1 expression and improving VC by regulating the ER pressure [ 89 ]. Interleukin enhancer binding factor 3 (ILF3) expression was found to be increased in calcified human aortic vascular smooth muscle cells (HAVSMCs) and calcified atherosclerotic plaques in humans and mice, and ILF3 promoted atherosclerotic calcification by acting on the promoter regions of BMP2 and STAT1 and mediating BMP2 upregulation and STAT1 downregulation, according to Fei Xie et al [ 90 ] BGP-15 is an emerging antidiabetic drug that has been found to inhibit Pi-induced phenotypic transformation during the osteochondrogenesis and mineralization of VSMCs, making it potentially ideal for reducing diabetic and nondiabetic vascular calcification [ 91 ]. In vitro experiments demonstrated that miR-223-3p blocked interleukin 6 (IL-6)/STAT3 signaling, thereby preventing osteogenic transformation and calcification in VSMCs [ 92 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Chen et al [ 306 ] showed that the calcium channel blocker verapamil inhibited the production and activity of calcifying EVs and also reduced the calcifying capacity of COL 1 to prevent ECM mineralization. BGP-15 is a new anti-diabetic drug candidate that increased MGP content and decreased Annexin A2 content in EVs and prevented calcium deposition in the ECM [ 307 ]. Alendronate (ALE), a bone resorption inhibitor, down-regulated the release of aged bone-EVs in VD3-treated aged mice to reduce the ovariectomy-induced VC [ 10 ].…”
Section: Treatment Strategy Of Vascular Calcification Based On "Cross...mentioning
confidence: 99%